ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIS DALAM PEMECAHAN MASALAH MATEMATIKA SESUAI DENGAN GAYA KOGNITIF DAN GENDER - Pratiwi, Dona Dinda (Universitas Islam Raden Intan Lampung, INDONESIA, 2015)
SMPN 1 Batanghariin the second semester of the academic year 2012/2013. They were two students who had field dependence cognitive style and two students who had field independence cognitive style. The subjects were taken by using the purposive sampling technique. The data of this research were gathered through think aloud method. The data were then analyzed by using the technique with the procedureas follows: (1) the data were classified on the basis of the indicators of mathematical communication after the data had been obtained from the first and the second collections; (2) the data were presented in table form; and (3) the conclusions were drawn. The validity of the data was conducted by using time triangulation. The result of this research were analyzed by using constant comparison in which subject in i (i= 1, 2) with the j (j= 1, 2) cognitive style which was already valid as well compared with subject in k (k= 1, 2) with the the j (j= 1, 2) cognitive style which was already valid as well. The equal ability of mathematical communication was made the main finding wheares the different ability of mathematical communication was made the other finding. The result of this research valid because of the dependability proved. The ability of mathematical communication of the students with the field dependence cognitive style is different from that of those with the field independence cognitive style. The students with the field dependence cognitive style can communicate the ideas in written way well but they have difficulties in communicating ideas in spoken way as well as inclination to receive information without reorganizing it in such a way that the problem-solving ideas presented cannot reveal the actual problem solution. Meanwhile, the students with the field independence cognitive style can communicate the ideas well in both spoken and written ways and process as well as reorganize information in such a way that the problem-solving ideas presented can reveal the actual problem solution.